Global Stages, Local Narratives: Theatrical Encounters through Selim Al Deen’s ’SwarnaBoal’ - Chakroborthy, Sudip (Jagannath University Journal of Arts, 2026)
This study undertakes a comprehensive examination of the intercultural dynamics of global theatre through an in-depth analysis of Selim Al Deen’s SwarnaBoal (The Golden Catfish), a seminal Bangla play that epitomises intercultural convergence. Employing a practice-based research approach, this investigation elucidates the mechanisms by which SwarnaBoal navigates international theatrical interactions while preserving the integrity of local cultural narratives. The play’s distinctive amalgamation of traditional Bangla narrative structures and contemporary global theatrical expressions has facilitated its global dissemination, as exemplified by its 2024 performance at Goldsmiths, University of London. Key findings underscore the intercultural exchange fostered by SwarnaBoal’s theatrical presentation, thereby showcasing its potential as a paradigmatic exemplar for global theatrical encounters. The study’s results have profound implications for future global theatre collaborations, emphasising the imperative of cross-cultural comprehension and dialogue in performance. As Gilbert (2018) astutely observes, intercultural theatre practices possess the capacity to facilitate global understanding and empathy, while Schechner (2004) posits that performance serves as a critical site for negotiating cultural meanings and identities. Through an examination of SwarnaBoal’s intercultural dynamics, this research contributes to the ongoing discourse on global theatre practices, highlighting the potential for local narratives to inform and enrich global cultural landscapes. Jagannath University Journal of Arts, v-15, i-2, 2025:p137-147